Pakistan Registry of Intensive CarE (PRICE): Expanding a lower middle-income, clinician-designed critical care registry in South Asia. (August 2019) - Hashmi, M; Beane, A; Taqi, A; Memon, MI; Athapattu, P; Khan, Z; Dondorp, AM; Haniffa, R
Introduction: In resource-limited settings – with inequalities in access to and outcomes for trauma, surgical and critical care – intensive care registries are uncommon. Aim: The Pakistan Society of Critical Care Medicine, Intensive Care Society (UK) and the Network for Improving Critical Care Systems and Training (NICST) aim to implement a clinician-led real-time national intensive care registry in Pakistan: the Pakistan Registry of Intensive CarE (PRICE). Method: This was adapted from a successful clinician co-designed national registry in Sri Lanka; ICU information has been linked to real-time dashboards, providing clinicians and administrators individual patient and service delivery activity respectively. Output: Commenced in August 2017, five ICU's (three administrative regions – 104 beds) were recruited and have reported over 1100 critical care admissions to PRICE. Impact and future: PRICE is being rolled out nationally in Pakistan and will provide continuous granular healthcare information necessary to empower clinicians to drive setting-specific priorities for service improvement and research.